Febrile Seizures among Children Admitted to the Department of Paediatrics of a Tertiary Care Centre: A Descriptive Cross-sectional Study - Sumita Poudel; Sudhir Adhikari; Rohit Thapa; Biraj Parajuli; Shanti Regmi; Prajjwal Kunwar (Journal of Nepal Medical Association, 2022)
Introduction: Febrile seizure is the most common convulsive event in children younger than 60 months. Fever plays an important role in causing disturbances in fluid and electrolyte balance, also hyponatremia has been thought to enhance the susceptibility to seizures. The objective of this study is to find out the prevalence of febrile seizures among children admitted to the Department of Paediatrics of a tertiary care centre.